Riparian biota of the Protected Area of Flora and Fauna Santa Elena Canyon, Mexico - Gatica Colima, Ana Bertha (2020)
The Protected Area of Flora and Fauna Santa Elena Canyon (Chihuahua, Mexico) has a national and international importance due to its flora and fauna, the contrast of its ecosystems and landscape resources, fostering a concern for its conservation. The objective of this study was to register species of birds, land mammals, fish and vegetation of the riparian zone at three locations within the protected area. Birds monitoring was conducted by no fixed radius count points, Sherman traps, trail cams and transect lines were used for land mammals, fish were monitored using manual fishing techniques and fishing spoon nets and finally the vegetation was recorded by means of interception lines. Field work was performed from December 2017 to December 2018. Among the four biological groups, a total of 166 species were recorded. Fauna: 73 birds, 24 land mammals and two fish species; flora: 67 species. Of the species we found 13.85 % are listed in the NOM-059-SEMARNAT-2010; 69.87 % were listed on the IUCN Red List of Threatened Species and 34 species were not included within the Management Program of the area. This study highlighted the need for systematic monitoring to increase knowledge and promote the conservation of the Protected Area of Flora and Fauna from Santa Elena Canyon in the future.